SOCIAL OPINION OF THE MINISTRY OF INTERNAL AFFAIRS ON PHYSICAL TRAINING OF STUDENTS OF ACADEMIC LYCEUMS - M. M. Makhmudova (Journals Park Publishing, 2022)
The concept of physical training of the students of the academic Lyceum of the Ministry of internal affairs was clarified through a Social Survey, the average statistical data were determined. The effectiveness of the methods used in the lessons of physical education was analyzed.
Keywords: academician of the lyceum; innovation